Dimensions of energy security in Small Island Developing States. (August 2018) - Raghoo, Pravesh; Surroop, Dinesh; Wolf, Franziska; Leal Filho, Walter; Jeetah, Pratima; Delakowitz, Bernd
Abstract: For Small Island Developing States (SIDS) that import oil, energy security is very important and dealt with seriously. This paper attempts to fill a gap in the literature by identifying the dimensions that shape a secure and sustainable supply of energy in SIDS. Seven dimensions were identified and incorporated into a framework for conceptualising and assessing SIDS energy security which are: import dependency; energy prices; climate change and resilience; governance; infrastructure; equity; and energy efficiency. This study also recommends selected strategies and actions to improve energy security in SIDS. Highlights: SIDS highly dependent on fossil fuels and severely exposed to energy security. Study reveals six energy security dimensions applicable to SIDS member states. Proposes potential strategies that can improve energy security in SIDS context. Study paramount for designing national energy policies in these states.